2014
DOI: 10.9790/0837-1985108111
|View full text |Cite
|
Sign up to set email alerts
|

Influences of gender on academic achievement of Fiber Optic Communication System: An experience of Politeknik Merlimau Melaka

Abstract: (t = 3.33, p <0.05). This means that female students have a mean significantly higher than male students in the achievement of a fiber optics communication system. However, this difference is very small. Apart from gender differences it also also found that other factors such as learning styles also contribute to students' academic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Various higher education institutions have reported inconsistent gender disparity patterns in academic performance 1 . As a result, several studies found that female students outperformed male students [2][3][4][5] . Studies show that the academic achievement gap between male and female graduates is not statistically significant [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Various higher education institutions have reported inconsistent gender disparity patterns in academic performance 1 . As a result, several studies found that female students outperformed male students [2][3][4][5] . Studies show that the academic achievement gap between male and female graduates is not statistically significant [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%